Situation Report: Poland, 17 February 1966 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Intense Attacks on Episcopate Meeting of the Main Council of ZBoWiD Wladyslaw Tykocinski Sentenced to Death Vice-Premier Jaroszewicz on Comecon Trade Protocol with Austria, Italy, Romania and Trade Agreement with Albania Trade News